Precise phylogenetic analysis of microbial isolates and genomes from metagenomes using PhyloPhlAn 3.0 - Francesco Asnicar (Nature Portfolio, 2020)
The increasing amount of sequenced microbial genomes and metagenomes requires platforms for efficient integrated analysis. Here, Asnicar et al. present PhyloPhlAn 3.0, a pipeline allowing large-scale microbial genome characterization and phylogenetic contextualization at multiple levels of resolution.